Guilty Property: A quantitative analysis of civil asset forfeiture - Warchol, Greg L. (American journal of criminal justice, 1996)
The objective of this article is to explore how property seized under the federal civil-judicial forfeiture laws for drug law violations is proceeded against by the government. The methodology is primarily exploratory. A sample of federal civil-judicial drug forfeiture cases is described and then analyzed in regard to the relative importance of the cases’ characteristics. The findings raise serious questions about the use of this policy and the government’s intent behind forfeiture. Implications and suggestions for future research are also presented.